2022
DOI: 10.1371/journal.pone.0263314
|View full text |Cite
|
Sign up to set email alerts
|

Road-based line distance surveys overestimate densities of olive baboons

Abstract: Estimating population density and population dynamics is essential for understanding primate ecology and relies on robust methods. While distance sampling theory provides a robust framework for estimating animal abundance, implementing a constrained, non-systematic transect design could bias density estimates. Here, we assessed potential bias associated with line distance sampling surveys along roads based on a case study with olive baboons (Papio anubis) in Lake Manyara National Park (Tanzania). This was achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 77 publications
(97 reference statements)
1
8
1
Order By: Relevance
“…Along the infrastructure corridor which includes the SGR, food leftovers are often thrown out of cars, particularly in areas close to human habitation (Lala, pers observation). This is likely to attract baboons towards roads and their greater use of wildlife corridors near roads 99 . Moreover, baboons’ proclivity for using wildlife corridors near roads can be further explained by their use of roads as an efficient method of travel, where groups of baboons can move faster and in a more directed manner 100 .…”
Section: Discussionmentioning
confidence: 99%
“…Along the infrastructure corridor which includes the SGR, food leftovers are often thrown out of cars, particularly in areas close to human habitation (Lala, pers observation). This is likely to attract baboons towards roads and their greater use of wildlife corridors near roads 99 . Moreover, baboons’ proclivity for using wildlife corridors near roads can be further explained by their use of roads as an efficient method of travel, where groups of baboons can move faster and in a more directed manner 100 .…”
Section: Discussionmentioning
confidence: 99%
“…As field survey and analytical methods varied among sites, it is, however, difficult to compare estimates among studies. Furthermore, comparative studies on olive baboon survey methods in LMNP provide evidence that distance sampling along roads yields biased absolute population density estimates (Kiffner et al, 2022). Manyara monkey densities (average of 13.0 individuals km −2 ; 95 % CI: 10.2-16.7) for LMNP are, at least, well within the range of densities for gentle monkeys at other sites in central Africa and eastern Africa (Butynski, 1990;Thomas, 1991;Plumptre and Reynolds, 1994;Fashing and Cords, 2000;Hall et al, 2003;Uehara, 2003;Fashing et al, 2012;McLester et al, 2019).…”
Section: Primate Densities In Contextmentioning
confidence: 92%
“…Before providing further interpretations of our data for conservation assessments, a word of caution is appropriate. As our density estimates are based on road surveys (which may not represent the entire study area; Kiffner et al, 2022) and as both monkey species showed distinct distribution patterns (which are not accounted for when extrapolating densities from the area covered by the transect to the study area), the actual population density of the surveyed species may differ from our estimates. Potential design-based bias probably does not affect temporal trends, but the non-random distribution of transects can substantially affect absolute density estimates (Beaver et al, 2014;Kiffner et al, 2017).…”
Section: Conservation Implicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…We chose a normal distribution for ϕ t because we assumed there to be an equal chance of underestimating or overestimating population abundance. The LPI uses a mix of survey types and estimation methods and there does not seem to be conclusive evidence of whether one type of bias is dominant (e.g., Johansson et al, 2020; Kiffner et al, 2022; Lubow & Ransom, 2016; Manning & Goldberg, 2010).…”
Section: Methodsmentioning
confidence: 99%